Nonlinear fibre element modelling of RC bridge piers considering inelastic buckling of reinforcement. (1st June 2016) - Kashani, Mohammad M.; Lowes, Laura N.; Crewe, Adam J.; Alexander, Nicholas A.
Highlights: Modelling nonlinear behaviour of RC columns using fibre technique. Simulation of bar buckling inside RC columns. Impact of inelastic buckling on cyclic response of RC columns. Modelling low-cycle fatigue degradation of RC columns. Abstract: An advanced modelling technique is developed to model the nonlinear cyclic response of circular RC columns using fibre-based section discretisation method. A comparison between different reinforcing steel models is made. Through a comprehensive parametric study the influence of inelastic buckling of vertical reinforcement on the cyclic response of circular RC columns is investigated. The results have been compared and validated against a set of experimental datasets. The proposed calibrated model accounts for the influence of inelastic buckling of vertical reinforcement and interaction of stiffness of horizontal ties reinforcement with vertical reinforcement. The model also accounts for the fracture of vertical bars due to low-cycle high-amplitude fatigue degradation. Therefore, this model is able to predict the nonlinear cyclic response of circular RC columns up to complete collapse. The results show that the existing uniaxial material models of reinforcing bars that are calibrated using stress–strain behaviour of isolated bars cannot represent the behaviour of reinforcing bars inside RC columns. Moreover, it is found that the buckling length of vertical reinforcement has a significant influence on the pinching response of RC columns and also reduces the low-cycle fatigue life of buckled reinforcement.